Coating method of electrode for ionic membrane electrolytic cell
By accurately control the electrode coating component and spraying process to ensure the uniformity and qualifications of the precious metal coating, the problem of incomplete control of precious metal Moore in the existing electrode production, improving the electrode performance and stability, reducing production cost.
Patent Information
- Application Number
- CN202411624223.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-24
AI Technical Summary
In the existing electrode production, the molar ratio control of precious metals such as ruthenium, iridium, platinum and other elements is not accurate enough, resulting in unstable electrode performance, shortened electrode life, and increased production costs.
By accurate analysis of the content of each component material in the formula, the conveyor -type production line is combined with the refractive electrostatic spraying device to spray precious metal coating to ensure the uniformity of the frame crystal of the grid of each unit, and the burning test to ensure the coating The qualifications of the layer.
Improve the performance detection indicators of the electrode, such as the weight gain, uniformity, potential, and enhanced life of the electrode, ensure the stability of the product quality and the smooth operation of the electrode on the ion membrane electrolytic groove, reducing the electrode cost.
Smart Images

Figure CN119352073A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode coatings, and in particular to a coating method for electrodes used in ion membrane electrolyzers. Background Art
[0002] The electrolytic process of caustic soda is to use ion membrane electrolyzers to electrolyze industrial salt water to produce caustic soda, hydrogen, chlorine and other products. The main costs are electricity consumption and salt. The DC power consumption of each ton of caustic soda is 2000 to 2400 degrees. In the chlor-alkali electrolysis process, the electrolysis process consumes the most electricity, accounting for about 80% to 90% of the total power consumption of the chlor-alkali process, and the energy consumption of the electrolyzer accounts for almost more than 95% of the total consumption. As a high-energy-consuming industry, saving energy, improving efficiency, adopting new technologies, and achieving clean production are the country's industrial policies. To ensure the stable performance and energy consumption indicators of the membrane cell during its life, the key is the performance of the cathode and anode electrodes.
[0003] The electrode active coating is a precious metal coating applied on the cathode nickel woven mesh and the anode titanium expanded mesh. The chloride of the precious metal is converted into oxide crystals by thermal oxidation. The coating oxide crystal structure, coating uniformity, and coating-substrate bonding strength are crucial. In recent years, the price of precious metals such as ruthenium, iridium, and platinum have risen, and the cost has risen sharply. Precise control of the coating components and process of the cathode electrode and anode electrode of the electrolytic cell can effectively control costs and make the electrode performance more superior and stable.
[0004] In the current electrode production, there are defects: the molar ratio of precious metals such as ruthenium, iridium, and platinum is not controlled accurately enough, and the production process control is not strict enough, which is one of the reasons for the large voltage fluctuations in each unit cell, and also causes the electrode life to be shortened and the production and operation costs to increase.
[0005] Therefore, it is necessary to accurately control the components of the electrode coating to achieve the optimal component combination, thereby reducing the voltage fluctuation of each unit cell, improving the electrode performance, and extending the electrode service life. Summary of the invention
[0006] The object of the present invention is to provide a coating method for an electrode for an ion membrane electrolyzer to solve the above-mentioned background problems.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A coating method for an electrode for an ion membrane electrolyzer comprises the following steps:
[0009] Step S1: Analyze the exact content of each component raw material in the formula, convert and add the materials, accurately measure to ensure that the molar ratio of each element meets the formula, and generate oxide crystals with a rutile structure;
[0010] Step S2: spraying using a conveyor belt production line combined with a reciprocating electrostatic spraying device, accurately measuring the spraying amount, weighing the electrode mesh and detecting the uniformity of the precious metal content;
[0011] Step S3: firing the electrode mesh, and after the firing is completed, detecting the crystal morphology; comprising:
[0012] SS31: Mark the points of the fired electrode mesh. Specifically, select the end grid of the electrode mesh as the coordinate origin, establish a rectangular coordinate system with the horizontal direction of the electrode mesh as the x-axis and the vertical direction as the y-axis, and mark each unit grid as (x, y);
[0013] SS32: Get the border crystal thickness value set P of each unit grid (x, y), where the border crystal thickness value set P is {Hsz (x,y) , Hsy (x,y) , Hxz (x,y) , Hxy (x,y)};
[0014] Based on the border crystal thickness value set P, the average border crystal thickness HJ of the unit grid is calculated (x,y) ; At the same time, the extreme value CJ of the crystal thickness deviation of the frame of the unit grid (x, y) is calculated (x,y) ;
[0015] SS33: Get the qualified value range of border crystal thickness [HGmin, HGmax], and determine the number of values of border crystal thickness in the unit grid (x, y) that are within the qualified value range of border crystal thickness [HGmin, HGmax], recorded as n (x,y) ;
[0016] Based on the mean thickness of the frame crystal HJ (x,y) and the extreme value of the crystal thickness deviation of the frame CJ (x,y) Calculate the border crystal thickness state value WD of the unit grid (x, y) (x,y) ;
[0017] SS34: Get the border crystal thickness status value WD (x,y) The number of unit grids greater than the stable value WDY of the frame crystal thickness state is denoted as m;
[0018] At the same time, the standard deviation value BK of the frame crystal thickness state is calculated by the standard deviation formula;
[0019] Then calculate and obtain the crystal thickness value SBX of the electrode mesh border;
[0020] SS35: Compare the electrode mesh frame crystal thickness performance value SBX with the electrode mesh frame crystal thickness qualified value SHG to obtain the electrode mesh coating qualified signal or the electrode mesh coating unqualified signal.
[0021] As a further solution of the present invention: in step S2, the precious metal is one or more of ruthenium trichloride hydrochloride aqueous solution, iridium tetrachloride hydrochloride aqueous solution, and chloroplatinic acid.
[0022] As a further solution of the present invention: in step S2, the process of spraying using a conveyor belt production line combined with a reciprocating electrostatic spraying device is specifically as follows:
[0023] Design and customize the coating production line. The electrode mesh is placed flat on the conveyor belt and passes through the spray chamber. An electrostatic spray atomizer gun is installed on the top of the spray chamber. The electrostatic spray atomizer gun is located above the reciprocating machine. Under the action of air pressure and static electricity, the raw materials are evenly sprayed on the substrate mesh. The material of the substrate mesh is nickel or titanium.
[0024] As a further solution of the present invention: in step S2, the steps of accurately measuring the spraying amount, weighing the electrode mesh and detecting the uniformity of the precious metal content specifically include:
[0025] Start spraying from one end of the substrate mesh. During the repeated spraying process, weigh once every two sprayings to track the coating amount and detect the precious metal content at each detection point on the electrode mesh.
[0026] As a further solution of the present invention: in the step S2, the electrode substrate mesh passes through the spray chamber and then enters the hot air drying system, and after drying, it proceeds to step S3 for sintering.
[0027] As a further solution of the present invention: in the step S3, a medium temperature furnace is used to burn the coated electrode mesh, wherein the medium temperature furnace is equipped with a stirring fan and PLC temperature control, and the temperature difference between each area in the medium temperature furnace is less than 5°C.
[0028] As a further solution of the present invention: in the SS32, the average value of the frame crystal thickness HJ (x,y) The calculation method is:
[0029]
[0030] The method for obtaining the extreme value of the frame crystal thickness deviation is:
[0031] Get the maximum value in the border crystal thickness value set P, recorded as the maximum border crystal thickness Hd (x,y) , and at the same time obtain the minimum value in the border crystal thickness value set P, recorded as the minimum border crystal thickness value Hx (x,y) ;
[0032] By CJ (x,y) =Hd (x,y) -Hx (x,y) Calculate the extreme value of the frame crystal thickness deviation CJ (x,y) .
[0033] As a further solution of the present invention: the frame crystal thickness state value WD in the SS33 (x,y) The calculation method is:
[0034]
[0035] As a further solution of the present invention: in the SS34, the calculation method of the crystal thickness performance value SBX of the electrode mesh is: Wherein, a is the stability coefficient of the frame crystal thickness state, b is the standard coefficient of the frame crystal thickness state, 0<a<1, 0<b<1, and a+b=1.
[0036] As a further solution of the present invention: in the SS35, the electrode mesh frame crystal thickness performance value SBX is compared with the electrode mesh frame crystal thickness qualified value SHG:
[0037] If the electrode mesh frame crystal thickness performance value SBX is greater than or equal to the electrode mesh frame crystal thickness qualified value SHG, a qualified signal of the electrode mesh coating is generated;
[0038] If the electrode mesh frame crystal thickness performance value SBX is less than the electrode mesh frame crystal thickness qualified value SHG, an electrode mesh coating unqualified signal is generated.
[0039] Beneficial effects of the present invention:
[0040] 1. In the present invention, the performance of the electrode product is tested in four aspects: electrode weight gain, uniformity, potential and enhanced life performance are significantly improved; the quality of the produced product is stable, the online operation performance is improved and the operation is stable when installed on the ion membrane electrolyzer; the electrode cost is effectively controlled;
[0041] 2. In the present invention, by detecting the coating thickness on the surface of the electrode mesh, the crystal thickness performance value of the coating on the surface of the electrode mesh after firing is calculated, and further judging whether the firing of the electrode mesh meets the qualified requirements, so as to ensure the stability rate and qualified rate in the production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The present invention will be further described below in conjunction with the accompanying drawings.
[0043] Figure 1 Schematic diagram of the upper surface structure of the substrate web;
[0044] Figure 2 Schematic diagram of the lower surface structure of the substrate web;
[0045] Figure 3 Schematic diagram of the substrate net coated with an anode coating for an ion-exchange membrane electrolyzer Figure 1 ;
[0046] Figure 4 Schematic diagram of the substrate net coated with an anode coating for an ion-exchange membrane electrolyzer Figure 2 ;
[0047] Figure 5 It is a flow chart of the coating detection method in the present invention;
[0048] Figure 6 It is a schematic diagram indicating the coordinates of the electrode network;
[0049] Figure 7 It is a block diagram of the coating burning detection and evaluation system in the present invention. DETAILED DESCRIPTION
[0050] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Embodiment 1
[0052] See also Figure 1-Figure 4 As shown, the present invention is a coating method for an electrode for an ion membrane electrolyzer, comprising the following steps:
[0053] Step S1: Analyze the exact content of each component raw material in the formula, convert and add the materials, accurately measure to ensure that the molar ratio of each element meets the formula, and generate oxide crystals with a rutile structure;
[0054] The precious metal raw materials selected for the formula, such as ruthenium trichloride hydrochloric acid aqueous solution, iridium tetrachloride hydrochloric acid aqueous solution, chloroplatinic acid, etc., have a range of error in the precious metal content of the factory products. If calculated according to the labeled content, it will cause an error in the molar ratio of the elements and affect the crystal structure. Through multiple sampling of each batch, using ICP (inductively coupled plasma spectrometer), spectrophotometer, X-ray fluorescence instrument and other precision instruments for analysis, the accurate content is determined and converted before feeding;
[0055] When taking materials according to the formula, use small-caliber measuring tools of 10 to 100 microliters and precision electronic scales, and compare the weighing with the empirical values to ensure the accurate measurement of the raw materials;
[0056] Step S2: spraying using a conveyor belt production line combined with a reciprocating electrostatic spraying device, accurately measuring the spraying amount, weighing the electrode mesh and detecting the uniformity of the precious metal content;
[0057] Design and customize the coating production line. The electrode net is placed flat on the conveyor belt and passes through the spray room. The electrostatic spray atomizer gun on the top of the spray room is installed on the reciprocating machine. The raw materials are evenly sprayed on the substrate net under the action of air pressure and static electricity. The substrate net is made of nickel and titanium. A material collection bin is set under the substrate net. The small amount of raw materials that pass through the mesh can be collected and processed for reuse;
[0058] Set up a special weighing room with shock-absorbing, wind-free, accurate electronic scales, etc. Starting from the substrate web, weigh it every two times during the repeated spraying process to track the coating amount, and use an X-ray fluorescence instrument to detect whether the precious metal content at each point of the electrode is uniform;
[0059] The electrode substrate mesh directly enters the hot air drying system after passing through the spraying room, and then enters the firing or sintering stage. The production workshop is equipped with a fresh air system to control the temperature, humidity and environmental cleanliness to prevent moisture and impurity pollution;
[0060] Step S3: firing the electrode mesh, and after the firing is completed, detecting the crystal morphology;
[0061] Use a high-power (50kW-200kW) medium-temperature furnace to burn and sinter the coated electrode mesh. The medium-temperature furnace is equipped with a high-power (10kW-100kW) stirring fan and PLC temperature control. Regularly use a patrol meter to check the temperature difference in each area of the furnace to be controlled within 5°C. Use comprehensive thermal analyzers, precision microscopes and other test analyses to determine the best heating, insulation and cooling curves. Combined with electrode performance analysis and testing, obtain an ideal catalyst layer structure;
[0062] Embodiment 2
[0063] Reference Figure 5 As shown, based on the above embodiment, this embodiment provides the following detection method for detecting the morphology of the crystal in step S3 in the above embodiment to ensure that an electrode mesh with a qualified coating is obtained:
[0064] Specifically include:
[0065] SS31: Mark the points of the fired electrode mesh. Specifically, select the end grid of the electrode mesh as the coordinate origin, establish a rectangular coordinate system with the horizontal direction of the electrode mesh as the x-axis and the vertical direction as the y-axis, and mark each unit grid as (x, y); Figure 6 As shown; Figure 6 It is a schematic diagram indicating the coordinates of the electrode network;
[0066] SS32: Get the border crystal thickness value set P of each unit grid (x, y), where the border crystal thickness value set P is {Hsz (x,y) , Hsy (x,y) , Hxz (x,y) , Hxy (x,y)};
[0067] Based on the border crystal thickness value set P, Calculate the mean crystal thickness HJ of the unit grid frame (x,y) ;
[0068] At the same time, the maximum value in the border crystal thickness value set P is obtained, and recorded as the maximum value of the border crystal thickness Hd (x,y) , and at the same time obtain the minimum value in the border crystal thickness value set P, recorded as the minimum border crystal thickness value Hx (x,y) ;
[0069] By CJ (x,y) =Hd (x,y) -Hx (x,y) Calculate the extreme value CJ of the crystal thickness deviation of the frame of the unit grid (x, y) (x,y) ;
[0070] SS33: Get the qualified value range of border crystal thickness [HGmin, HGmax], and determine the number of values of border crystal thickness in the unit grid (x, y) that are within the qualified value range of border crystal thickness [HGmin, HGmax], recorded as n (x,y) ;
[0071] Based on the mean thickness of the frame crystal HJ (x,y) and the extreme value of the crystal thickness deviation of the frame CJ (x,y) ,pass Calculate the border crystal thickness state value WD of the unit grid (x, y) (x,y) ;
[0072] SS34: Get the border crystal thickness status value WD (x,y) The number of unit grids greater than the stable value WDY of the frame crystal thickness state is denoted as m;
[0073] At the same time, the standard deviation value BK of the frame crystal thickness state is calculated by the standard deviation formula;
[0074] Then through Calculate and obtain the frame crystal thickness performance value SBX of the electrode mesh, where a is the frame crystal thickness state stability coefficient, b is the frame crystal thickness state standard coefficient, 0<a<1, 0<b<1, and a+b=1;
[0075] SS35: Compare the electrode mesh frame crystal thickness performance value SBX with the electrode mesh frame crystal thickness qualified value SHG:
[0076] If the electrode mesh frame crystal thickness performance value SBX is greater than or equal to the electrode mesh frame crystal thickness qualified value SHG, a qualified signal of the electrode mesh coating is generated;
[0077] If the electrode mesh frame crystal thickness performance value SBX is less than the electrode mesh frame crystal thickness qualified value SHG, an electrode mesh coating unqualified signal is generated.
[0078] By testing the coating thickness on the surface of the electrode mesh, the crystal thickness performance value of the coating on the surface of the electrode mesh after firing is calculated, and further judging whether the firing of the electrode mesh meets the qualified requirements, so as to ensure the stability rate and qualified rate in the production process.
[0079] In addition, the electrode mesh prepared by the above scheme was experimentally tested:
[0080] Experimental test results:
[0081] Chlorine evolution potential of anode coating: 1.07V~1.10V. (Control standard: ≤1.13V, current density: 4kA / m 2 , reference electrode: Vs.SEC, saturated brine, temperature: 90℃±1℃);
[0082] Anode coating life test: <1.5mg. (Control standard: weight loss <6.3mg, test conditions: 30% WtNaOH solution (CP grade), test piece 10cm 2 , temperature 90℃±1℃, current density 20kA / m 2 , electrolysis for 4 hours);
[0083] Hydrogen evolution potential of cathode coating: 1.20V~1.25V. (Control standard: ≤1.35V, test piece 50mm*50mm, current density: 4kA / m 2 , reference electrode: Vs.SEC, 32% WtNaOH solution (CP grade), temperature: 90℃±1℃)
[0084] Cathode coating life test: <4.0mg. (Control standard: weight loss <16mg, test piece specification 100mm*50mm, test conditions: current density: 4kA / m 2 , conduct a 120-hour electrolysis life test, electrolyze for 4 hours and cut off the power for 1 hour, electrolyze for a total of 96 hours, cut off the power 24 times for a total of 24 hours, weigh with an electronic balance to obtain the weight loss before and after electrolysis);
[0085] Combined with the experimental test results, it can be concluded that the voltage is significantly reduced, which can reduce power consumption, reduce weight loss, and extend the service life. That is, the four performance tests of the electrode product: electrode weight gain, uniformity, potential and enhanced life performance are significantly improved; the quality of the production products is stable, and the online operation performance installed on the ion membrane electrolyzer is improved and the operation is stable; the electrode cost is effectively controlled.
[0086] Embodiment 3
[0087] Reference Figure 7 As shown, based on the above embodiment, this embodiment provides a motor network surface coating burn-in detection and evaluation system, including:
[0088] Area calibration module: mark the points of the electrode mesh after firing. Specifically, select the grid at the end of the electrode mesh as the coordinate origin, establish a rectangular coordinate system with the horizontal direction of the electrode mesh as the x-axis and the vertical direction as the y-axis, and mark each unit grid as (x, y);
[0089] Data acquisition module: obtain the border crystal thickness value set P of each unit grid (x, y), where the border crystal thickness value set P is {Hsz (x,y) , Hsy (x,y) , Hxz (x,y) , Hxy (x,y)};
[0090] Based on the border crystal thickness value set P, the average border crystal thickness HJ of the unit grid is calculated (x,y) ; At the same time, the extreme value CJ of the crystal thickness deviation of the frame of the unit grid (x, y) is calculated (x,y) ;
[0091] Data processing module: obtain the qualified value range of border crystal thickness [HGmin, HGmax], determine the number of values of border crystal thickness in the unit grid (x, y) that are within the qualified value range of border crystal thickness [HGmin, HGmax], recorded as n (x,y) ;
[0092] Based on the mean thickness of the frame crystal HJ (x,y) and the extreme value of the crystal thickness deviation of the frame CJ (x,y) Calculate the border crystal thickness state value WD of the unit grid (x, y) (x,y) ;
[0093] Data analysis module: Get the border crystal thickness status value WD (x,y) The number of unit grids greater than the stable value WDY of the frame crystal thickness state is denoted as m;
[0094] At the same time, the standard deviation value BK of the frame crystal thickness state is calculated by the standard deviation formula;
[0095] Then calculate and obtain the crystal thickness value SBX of the electrode mesh border;
[0096] Evaluation module: compare the electrode mesh frame crystal thickness performance value SBX with the electrode mesh frame crystal thickness qualified value SHG to obtain a qualified signal of the electrode mesh coating or an unqualified signal of the electrode mesh coating.
[0097] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A coating method for an electrode for an ion membrane electrolyzer, characterized in that: The steps include: Step S1: Analyze the exact content of each component raw material in the formula, convert and add the materials, accurately measure to ensure that the molar ratio of each element meets the formula, and generate oxide crystals with a rutile structure; Step S2: spraying using a conveyor belt production line combined with a reciprocating electrostatic spraying device, accurately measuring the spraying amount, weighing the electrode mesh and detecting the uniformity of the precious metal content; Step S3: firing the electrode mesh, and after the firing is completed, detecting the crystal morphology; include: SS31: Mark the points of the fired electrode mesh. Specifically, select the end grid of the electrode mesh as the coordinate origin, establish a rectangular coordinate system with the horizontal direction of the electrode mesh as the x-axis and the vertical direction as the y-axis, and mark each unit grid as (x, y); SS32: Get the border crystal thickness value set P of each unit grid (x, y), where the border crystal thickness value set P is {Hsz (x,y) , Hsy (x,y) , Hxz (x,y) , Hxy (x,y) }; Based on the border crystal thickness value set P, the average border crystal thickness HJ of the unit grid is calculated (x,y) ; At the same time, the extreme value CJ of the crystal thickness deviation of the frame of the unit grid (x, y) is calculated (x,y) ; SS33: Get the qualified value range of border crystal thickness [HGmin, HGmax], and determine the number of values of border crystal thickness in the unit grid (x, y) that are within the qualified value range of border crystal thickness [HGmin, HGmax], recorded as n (x,y) ; Based on the mean thickness of the frame crystal HJ (x,y) and the extreme value of the crystal thickness deviation of the frame CJ (x,y) Calculate the border crystal thickness state value WD of the unit grid (x, y) (x,y) ; SS34: Get the border crystal thickness status value WD (x,y) The number of unit grids greater than the stable value WDY of the frame crystal thickness state is denoted as m; At the same time, the standard deviation value BK of the frame crystal thickness state is calculated by the standard deviation formula; Then calculate and obtain the crystal thickness value SBX of the electrode mesh border; SS35: Compare the electrode mesh frame crystal thickness performance value SBX with the electrode mesh frame crystal thickness qualified value SHG to obtain the electrode mesh coating qualified signal or the electrode mesh coating unqualified signal.
2. The coating method for an ion-exchange membrane electrolyzer electrode according to claim 1, characterized in that: In step S2, the noble metal is one or more of ruthenium trichloride hydrochloric acid aqueous solution, iridium tetrachloride hydrochloric acid aqueous solution, and chloroplatinic acid.
3. The coating method for an ion membrane electrolyzer electrode according to claim 1, characterized in that: In step S2, the process of spraying using a conveyor belt production line combined with a reciprocating electrostatic spraying device is specifically as follows: Design and customize the coating production line. The electrode mesh is placed flat on the conveyor belt and passes through the spray chamber. An electrostatic spray atomizer gun is installed on the top of the spray chamber. The electrostatic spray atomizer gun is located above the reciprocating machine. Under the action of air pressure and static electricity, the raw materials are evenly sprayed on the substrate mesh. The material of the substrate mesh is nickel or titanium.
4. The coating method for an ion-exchange membrane electrolyzer electrode according to claim 1, characterized in that: In step S2, the steps of accurately measuring the spraying amount, weighing the electrode mesh and detecting the uniformity of the precious metal content specifically include: Start spraying from one end of the substrate mesh. During the repeated spraying process, weigh once every two sprayings to track the coating amount and detect the precious metal content at each detection point on the electrode mesh.
5. The coating method for an ion membrane electrolyzer electrode according to claim 1, characterized in that: In the step S2, the electrode substrate mesh enters the hot air drying system after passing through the spraying room, and after drying, it enters the step S3 for sintering.
6. The coating method for an ion membrane electrolyzer electrode according to claim 1, characterized in that: In step S3, the coated electrode mesh is fired in a medium temperature furnace, wherein the medium temperature furnace is equipped with a stirring fan and PLC temperature control, and the temperature difference between each area in the medium temperature furnace is less than 5°C.
7. The coating method for an electrode for an ion membrane electrolyzer according to claim 1, characterized in that: In the SS32, the average crystal thickness of the frame is HJ (x,y) The calculation method is: The method for obtaining the extreme value of the frame crystal thickness deviation is: Get the maximum value in the border crystal thickness value set P, recorded as the maximum border crystal thickness Hd (x,y) At the same time, the minimum value in the border crystal thickness value set P is obtained, which is recorded as the minimum border crystal thickness value Hx (x,y) ; By CJ (x,y) =Hd (x,y) -Hx (x,y) Calculate the extreme value of the frame crystal thickness deviation CJ (x,y) .
8. The coating method for an ion-exchange membrane electrolyzer electrode according to claim 1, characterized in that: The SS33 frame crystal thickness state value WD (x,y) The calculation method is:
9. The coating method for an electrode for an ion membrane electrolyzer according to claim 1, characterized in that: In the SS34, the calculation method of the crystal thickness performance value SBX of the electrode mesh is: Wherein, a is the stability coefficient of the frame crystal thickness state, b is the standard coefficient of the frame crystal thickness state, 0<a<1, 0<b<1, and a+b=1.
10. The coating method for an electrode for an ion membrane electrolyzer according to claim 1, characterized in that: In the SS35, the electrode mesh frame crystal thickness performance value SBX is compared with the electrode mesh frame crystal thickness qualified value SHG: If the electrode mesh frame crystal thickness performance value SBX is greater than or equal to the electrode mesh frame crystal thickness qualified value SHG, a qualified signal of the electrode mesh coating is generated; If the electrode mesh frame crystal thickness performance value SBX is less than the electrode mesh frame crystal thickness qualified value SHG, an electrode mesh coating unqualified signal is generated.